Metformin Protects H9C2 Cardiomyocytes from High-Glucose and Hypoxia/Reoxygenation Injury via Inhibition of Reactive Oxygen Species Generation and Inflammatory Responses: Role of AMPK and JNK - Mingyan Hu; Ping Ye; Hua Liao; Manhua Chen; Feiyan Yang (Journal of Diabetes Research)
Metformin is a first-line drug for the management of type 2 diabetes. Recent studies suggested cardioprotective effects of metformin against ischemia/reperfusion injury. However, it remains elusive whether metformin provides direct protection against hypoxia/reoxygenation (H/R) injury in cardiomyocytes under normal or hyperglycemic conditions. This study in H9C2 rat cardiomyoblasts was designed to determine cell viability under H/R and high-glucose (HG, 33 mM) conditions and the effects of cotreatment with various concentrations of metformin (0, 1, 5, and 10 mM). We further elucidated molecular mechanisms underlying metformin-induced cytoprotection, especially the possible involvement of AMP-activated protein kinase (AMPK) and Jun NH(2)-terminal kinase (JNK). Results indicated that 5 mM metformin improved cell viability, mitochondrial integrity, and respiratory chain activity under HG and/or H/R (P<0.05). The beneficial effects were associated with reduced levels of reactive oxygen species generation and proinflammatory cytokines (TNF-α, IL-1α, and IL-6) (P<0.05). Metformin enhanced phosphorylation level of AMPK and suppressed HG + H/R induced JNK activation. Inhibitor of AMPK (compound C) or activator of JNK (anisomycin) abolished the cytoprotective effects of metformin. In conclusion, our study demonstrated for the first time that metformin possessed direct cytoprotective effects against HG and H/R injury in cardiac cells via signaling mechanisms involving activation of AMPK and concomitant inhibition of JNK.